2013
DOI: 10.1016/j.jad.2013.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole augmentation to antidepressant therapy in Japanese patients with major depressive disorder: A randomized, double-blind, placebo-controlled study (ADMIRE study)

Abstract: Aripiprazole augmentation at a fixed or flexible dose was superior to ADT alone and was reasonably well tolerated in Japanese patients with inadequate response to ADT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
90
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(101 citation statements)
references
References 28 publications
10
90
1
Order By: Relevance
“…Our findings may reflect the carefulness of clinicians to minimize the potential AEs associated with QA. Indeed, the discontinuation rate of QA (20.9%) for any reason was also markedly higher than those from other antipsychotics (AA = 12.1%, risperidone augmentation = 16.3) (Nelson and Papakostas, 2009;Kamijima et al, 2013). For instance, the odds ratio of QA for discontinuation because of AEs was 4.85, which is markedly higher than those of other individual atypical antipsychotic and the whole antipsychotics together (aripiprazole = 2.38, olanzapine = 3.85, risperidone = 1.55, and whole antipsychotics = 3.32) (Wen et al, 2014).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our findings may reflect the carefulness of clinicians to minimize the potential AEs associated with QA. Indeed, the discontinuation rate of QA (20.9%) for any reason was also markedly higher than those from other antipsychotics (AA = 12.1%, risperidone augmentation = 16.3) (Nelson and Papakostas, 2009;Kamijima et al, 2013). For instance, the odds ratio of QA for discontinuation because of AEs was 4.85, which is markedly higher than those of other individual atypical antipsychotic and the whole antipsychotics together (aripiprazole = 2.38, olanzapine = 3.85, risperidone = 1.55, and whole antipsychotics = 3.32) (Wen et al, 2014).…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, there has been an increase in recent studies reporting the beneficial effects of lower doses of AA for the treatment of MDD particularly in Asian regions (Lin et al, 2011;Pae et al, 2011;Chen et al, 2012;Kamijima et al, 2013;Pae and Patkar, 2013;Patkar and Pae, 2013). In fact, the first large RCT of AA for an Asian population (Kamijima et al, 2013) has also found that a lower dose (3 mg/day) of AA should be more useful than a higher dose (mean dose = 9.8 mg/day) in terms of the risk and benefit aspect; however, such beneficial effects of lower dose of AA were not replicated in Western population studies (Mischoulon et al, 2012). Similarly, the efficacy of quetiapine XR of 50 mg/day as monotherapy was also proven in a three-dose arm study (Weisler et al, 2009) and it was also different from placebo in the change in the MADRS total score from baseline by day 4.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 5 years, the atypical antipsychotic agents have continued to expand their evidence base supporting their efficacy as adjunctive treatments in MDD (for a review, see Nelson and Papakostas 6 as well Kamijima et al 100 for the most recently published clinical trial). Indeed, at this time, olanzapine, aripiprazole and quetiapine represent the only pharmacological agents approved by the FDA as adjunctive therapies for use when standard antidepressants have failed to produce significant symptom improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the number of randomized patients was set at a total of 400 (200 in the ASC group and 200 in the PSC group), considering the potential number of patients excluded from the analysis. The planned number of patients enrolled in the prospective treatment period was 800 because in the four previous studies, approximately 50% of the patients who had been enrolled in the selective serotonin reuptake inhibitor/serotonin‐noradrenaline reuptake inhibitor treatment period subsequently proceeded to the double‐blind period …”
Section: Methodsmentioning
confidence: 99%
“…Aripiprazole is pharmacologically distinct from other antipsychotics, acting as a partial agonist at the dopamine D 2 , D 3 , and serotonin 5‐HT 1A receptors and as an antagonist at the 5‐HT 2A receptors . It is approved for use as an adjunctive treatment to ADT in adults with MDD on the basis of results from large, multicenter, randomized, double‐blind, placebo‐controlled studies in the USA and Japan . These studies demonstrated the efficacy of adjunctive aripiprazole in patients with an inadequate response to a prospective 8‐week treatment of the same ADT and at least one historical ADT treatment …”
mentioning
confidence: 99%